PEMBELAJARAN TRAINING INQUIRY MODEL DENGAN BANTUAN KWL CHART TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS SEBELAS MARET DALAM MATA KULIAH KONSTRUKSI BANGUNAN GEDUNG - Prasetiyanti, Tutut; Sutrisno, Sutrisno; Rahmawati, Anis (Pendidikan Teknik Bangunan, 2014)
Abstract: This researched is purposed to know applied of Training Inquiry Model with KWL Chart can increase of result study?s student of Sebelas Maret University in Building Construction Subject. This researched is class researched action besed on plan, done, observation, and reflection. Reseacrh?s subject is student of Building Engineering Education year 2012 that amount 31 student of university. Source of data from lecturer, student of university, books and literature. Technic to collect of data is used documentation and test. Learned before done is used conventional method and result student study of university just can mínimum completeness limit. Result this researched is proved that use Training Inquiry Model with KWL Chart can increase result of learned?s student of university in cognitive aspec is 75,92, affective aspec is 76,61, and psychomotor aspec is 79,03. The result of this researched is Training Inquiry Model studied with KWL Chart can increase result?s study of student of Building Engineering Education Sebelas Maret University in Building in cognitive aspec is 75,92, affective aspec is 76,61, and psychomotor aspec is 79,03.Keywords: conventional, Training Inquiry Model, KWL Chart, result of study